Integrating STEM education in sustained deep rural schools: innovative strategies for multi-grade, multi-subject classrooms - Jones, Devan A. (Frontiers in Education, 2025)
Sustained Deep Rurality (SDR) represents an extreme form of rurality, characterized by geographic isolation, small school populations, and limited access to resources. Despite these challenges, SDR educators play a crucial role in advancing STEM education in multi-grade, multi-curricular classrooms. This study investigates how SDR K-8 teachers in the Northern Rocky Mountain region implement STEM education amid constraints such as professional isolation, limited funding, and diverse student needs. Using narrative interviews and small story analysis, the research identifies three key strategies: (1) Planning for Multiple Grades and Subjects, (2) Multi-Subject Connections and there Contribution to Integrating STEM in SDR classrooms, and (3) Necessity and Utilization of Local Resources. Findings reveal that SDR educators employ innovative, place-based STEM methodologies, incorporating local ecosystems, agriculture, and industry to create relevant and engaging learning experiences. This study highlights the resilience and ingenuity of SDR teachers, offering insights into how STEM education can be effectively adapted for the most remote and underserved students, ultimately promoting educational equity in extreme rural contexts.